[Geyser Eruption] - Streng, Evelyn Fiedler (1975)
Photograph of a geyser eruption. The white, V-shaped geyser sits in a blue, brown rock lined pool of water in the foreground. Steam surrounds the geyser, moving to the left side of the photograph. A yellow plain lined with white fences are visible in the background past the geyser.